ZONULIN LEVELS IN COMPLICATED PREGNANCY : A SYSTEMATIC REVIEW - Syahputra Damanik, Roni Andre (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Hepatocytes, enterocytes, adipose tissue, and immune cells are the primary sources of zonulin secretion. It is the major protein responsible for the regulation of tight junctions between intestinal epithelial cells. Stimulating the release of zonulin dissociates zonula occludens-1 protein from tight junctions, resulting in increased intestinal permeability. Intestinal barrier failure has a role in gestational diabetes and intrahepatic cholestasis of pregnancy pathogenesis (ICP). Dietary decisions have a significant impact on intestinal permeability and, as a result, the risk of developing metabolic diseases. The inability of this experiment to account for dietary components and make the appropriate adjustments to the results is a drawback. Throughout the course of our experiment, we noticed that plasma zonulin levels and body mass index (BMI) were positively associated. On the other hand, the conclusions of the studies conducted on pregnant women are debatable. Individuals with problems of pregnancy, such as gestational diabetes, have elevated zonulin levels. As we all know, gestational diabetes can lead to macrosomia, birth canal trauma, and a future risk of diabetes for both mother and child.